VERTICAL PARKING BUILDING DESIGN WITH TROPICAL ARCHITECTURE ON PALANGKARAYA STREET, MEDAN CITY - Pikri Tindaon; Bhakti Alamsyah; Ramadani Fitri (INFOKUM, 2022)
In the global era, the economic growth of Indonesia is currently growing so investors are tempted to invest in Indonesia. It is predicted that in the next decade, the central business district and its surroundings will be full of high-rise buildings. The growth of the office buildings construction in Indonesia, especially in Medan, is facing serious problems, namely limited available land; high land-price; high density of activities which causing boredom for office employees. Those reasons are the background of office park concept (offices within the park) in Medan. The building must be able to adapt to the climate situation. The tropical architecture concept is applied so that the building will be able to adapt and be reactive to an unpredictable climate. At the end, the role of office park concept can provide alternative forms which paying attention to the ecology of the density office environment and can reduces the air temperature around it.